Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1002/esp.3290010304
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the random model of drainage basin composition

Abstract: SUMMARYThe random model of drainage basin composition is founded on the assumptions that (a) natural channels are topologically random in the absence of geological controls and (b) for channel networks developed in similar environments, the exterior and interior link lengths are independent random variables with a common distribution for each type. The effectiveness of this model in estimating the values of geomorphic variables and in explaining and predicting geomorphic relationships is illustrated by several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…This prediction is supported by the results of various investigations, particularly that of Werner and Smart (1976). The first step in our analysis of channel network composition, then, is an attempt to gain some insight into the topologic properties of the networks.…”
Section: Topologic Analysismentioning
confidence: 68%
See 2 more Smart Citations
“…This prediction is supported by the results of various investigations, particularly that of Werner and Smart (1976). The first step in our analysis of channel network composition, then, is an attempt to gain some insight into the topologic properties of the networks.…”
Section: Topologic Analysismentioning
confidence: 68%
“…Unfortunately, the data which he presented in its behalf were scant and not very convincing, and there has been little if any later work which supported it. Early work by Strahler and his students led Strahler (1952Strahler ( , p. 11361957, p. 914), to conclude that the bifurcation ratio was essentially independent of environment except in regions that have certain types of strong geological controls. Chorley (1957), in a morphometric study of three areas with widely different reliefs and drainage densities, found no significant differences in the bifurcation, length, or area ratios.…”
Section: Composition Implies the Numbers And Lengths Of Streams And Tmentioning
confidence: 97%
See 1 more Smart Citation
“…III Data structure Since Shreve (1966; identified the link as the fundamental network element it has become apparent that all the information extracted from a drainage network should be referenced to individual link locations. Some recent studies have reported very large link data sets: over 8700 link lengths by Smart and Werner (1976), and over ig6oo link lengths and azimuths by Jarvis (ig75). It is appropriate to devise some general data structure model, so that future link data sets may be both comparable between studies, and also, as far as possible, amenable to re-use when further new parameters are defined.…”
Section: Terminology and Conceptsmentioning
confidence: 99%
“…It is possible to argue that it is a theory, since work by the drainage network topology school (cf. Smart and Werner, 1976) appears to show the persistence of random patterns which are largely uninfluenced by variations in lithology, history or present-day intensity of processes.…”
mentioning
confidence: 93%